Analysis of the presence of bonding defects on the fracture behavior of a damaged plate repaired by composite patch (Fracture and Structural Integrity, 2019)
The repair technique has presented its effectiveness in the reduction of the stresses at the level of stresses concentration areas. The search for a patch and suitable adhesive for a good transfer of load has pushed researchers to develop many ideas, which relate the form, the nature, the stacking sequence of the patch and the adhesive type to give a better combination of choice between the patch and the adhesive. Our work fits in this context; the objective is to analyze by the method of finite elements the behavior in the rupture of a damaged plate in the presence of defect of bonding. The analysis of J-Integral and stresses in the tow substrates adhesive and patch shows clearly that their values depends strongly on the position of the default essentially when it’s located close to the free edge of the free edge of the adhesive or the crack.
Keywords: J-Integral; Adhesive defect; Peel stress; Shear stress